PENGARUH PEMANFAATAN KECERDASAN BUATAN (AI), SISTEM INFORMASI AKUNTANSI (SIA), DAN E-COMMERCE TERHADAP MINAT BERWIRAUSAHA PADA MAHASISWA AKUNTANSI PERGURUAN TINGGI NEGERI DI KABUPATEN SLEMAN - Dheka Putri Falisa (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Achmad Yani Yogyakarta, 2025)
This study aims to examine the influence of the utilization of Artificial Intelligence (AI), Accounting Information Systems (AIS), and E-Commerce on the entrepreneurial interest of accounting students at public universities in Sleman Regency. The background of this research is driven by the high unemployment rate among university graduates and the low level of entrepreneurial interest among students. Data were collected through the distribution of questionnaires to accounting students at four public universities in the Sleman area, with a total of 324 respondents. The collected data were analyzed using multiple linear regression with the assistance of SPSS software. The results of the study indicate that the utilization of AI, Accounting Information System, and E-Commerce has a positive and significant effect on entrepreneurial interest, both partially and simultaneously. These findings suggest that the use of digital technology can encourage students to develop their entrepreneurial potential. Keywords: Artificial Intelligence, Accounting Information Systems, E-Commerce, Entrepreneurial Interest, Students